2023
DOI: 10.3390/lubricants11040184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Third-Particle Material and Contact Mode on Tribology Contact Characteristics at Interface

Abstract: A moving pair with two-body contact is the ideal situation assumed in previous analyses. However, all moving pairs are in a three-body contact state at the start of operation or immediately after the start of operation, such as bearings, ball-screws, gears and engines. This work studies the influence of wear particles (SUJ2), environmental particles (SiO2 and Al2O3) and nano-additives (CuO) on the tribological contact characteristics under different particle concentrations, particle sizes, surface roughnesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Various operating conditions influence TPCA in 3-body dry contact conditions (Chern et al, 2022). Various foreign particles influence the contact characteristics of 3-body dry contact interfaces and validate the feasibility of the theory through four-ball experiments (Horng et al, 2023). In recent years, although there have been studies on the effect of different lubricant viscosities on surface friction (Vanossi et al, 2020) and wear (Tsai, 2024), most studies have focused on 2-body contact conditions.…”
Section: Property Valuementioning
confidence: 60%
See 1 more Smart Citation
“…Various operating conditions influence TPCA in 3-body dry contact conditions (Chern et al, 2022). Various foreign particles influence the contact characteristics of 3-body dry contact interfaces and validate the feasibility of the theory through four-ball experiments (Horng et al, 2023). In recent years, although there have been studies on the effect of different lubricant viscosities on surface friction (Vanossi et al, 2020) and wear (Tsai, 2024), most studies have focused on 2-body contact conditions.…”
Section: Property Valuementioning
confidence: 60%
“…Under different conditions, the relationship between the three contact modes and the A sa,t * are observed (Horng et al, 2023), as shown in Figure 2. Figure 2A shows the surface-to-surface 3-body contact mode (s-s mode).…”
Section: Classification Of 3-body Contact Modementioning
confidence: 94%
“…Nanoparticles (NPs) have attracted considerable research interest due to their unique mechanical and chemical properties, particularly in the fields of nano-lubrication [1][2][3][4][5][6] and ultraprecision manufacturing [7][8][9][10][11][12]. Since the friction, wear, and energy loss between two mating surfaces of a friction couple are closely related to the motion state (sliding or rolling) of the third NPs [3,5,11], the comprehensive investigations into the tribological and dynamic behaviors of NPs motion have become essential.…”
Section: Introductionmentioning
confidence: 99%